A Critical Review of the Literature Regarding the Selection of Long-Term Romantic Partners - Devenport, Scott; Davis-McCabe, Catriona; Winter, Sam (2023)
Research regarding how people choose their long-term romantic partners is extensive, but the understanding of the psychological processes behind these choices, and predicting who people choose, is elusive. This review attempts to examine potential reasons for this elusive nature by first outlining the current state of the literature and then highlighting issues within the current paradigm. First among these issues is a focus on singular perspectives and little attempt to integrate these perspectives with others. Second, many studies focus on increasingly complex designs to explore the predictive utility of trait preferences, attempts which have had only limited success. Third, novel findings appear to be unintegrated with established findings, leaving the potential combination of these ideas unrealized. Finally, long-term romantic partner selection is a complex psychological phenomenon, but current theory and research methodologies are not sufficiently addressing this complexity. This review concludes with suggestions for future research direction, including a focus on the psychology behind the partner selection process and the potential of qualitative enquiry to reveal novel pathways behind these psychological processes. There is a need for an integrative framework that permits the coexistence of established and novel ideas, and multiple perspectives, from both current and future research paradigms.